Respon Pertumbuhan Stek Jeruk Pamelo Akibat Perlakuan Media Tanam Dan ZPT Akar : Growth Response of Pamelo Orange Cuttings Due to Planting Media and Root PGR Treatment - Indah Yuliani; Widiwurjani, Widiwurjani (Agrocentrum, 2024)
Pomelo is a type of orange that has distinctive characteristics, namely large size, sweet taste and has prospects for development. This study aims to determine the effect of planting media and the provision of root growth regulators on the growth of pomelo plant cuttings. The study was conducted in Setren Village, Ngasem District, Bojonegoro in January-March 2024. The study was arranged using a Randomized Block Design (RAK) with two factors. The first factor is the planting media with 3 levels of soil treatment + rice husk charcoal + cow manure (1:1:1), (1:2:1), and (1:1:2). While the second factor is the provision of Rootone-F with 2 levels of treatment 0 and 2 grams. Observation parameters include when shoots appear, number of shoots, shoot height, number of roots, and root length. The best combination treatment results were obtained from the M3R1 treatment (soil + rice husk charcoal + cow manure 1:1:2 and Rootone-F 2 grams).